2008
DOI: 10.1111/j.1399-6576.2008.01759.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pre‐operative fluid infusion on volume status during oesophageal resection – a prospective trial

Abstract: Pre-operative i.v. fluid loading with crystalloid solutions could not be shown to improve the intraoperative volume status and cardiac function in this study. Randomised trials with other volume replacement techniques are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
1
0
2
Order By: Relevance
“…Other groups have suggested that a preoperative crystalloid substitution offers no benefit for the patient [ 28 ] . In these studies, CO was examined only in the observation by Raue et al [ 26 ] . They found that standard monitoring in awake patients offered no reliable information regarding the ideal timing or ideal amount of volume substitution needed.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have suggested that a preoperative crystalloid substitution offers no benefit for the patient [ 28 ] . In these studies, CO was examined only in the observation by Raue et al [ 26 ] . They found that standard monitoring in awake patients offered no reliable information regarding the ideal timing or ideal amount of volume substitution needed.…”
Section: Discussionmentioning
confidence: 99%
“…Eine verspätete Korrektur ist jedoch mit negativen Auswirkungen auf das Outcome der Patienten assoziiert [7,16,17]. Wie lässt sich also die Hypovolämie im klini- [39].…”
Section: Hämodynamisches Managementunclassified
“…In der elektiven Viszeralchirurgie wurden negative Auswirkungen umfänglicher Volumensubstitution für die Heilung von gastrointestinalen Anastomosen und die Inzidenz von postoperativen Komplikationen belegt [2,3,4]. Somit stellt sich gerade bei der abdominellen Sepsis auch die Frage: «Wie viel Volumen ist genug?» Oder anders ausgedrückt: Sind Anasarka und «Fluid Lung» nach Therapie des septischen Schocks bei kapillärem Leck-Syndrom ein lässlicher Schönheitsfehler oder relevant für Morbidität und Mortalität der Patienten?…”
Section: Introductionunclassified